Хірургічна корекція істміко-цервікальної недостатності при невиношуванні вагітності = Surgical correction of isthmic-cervical insuffiency at miscarriage of pregnancy - Makarenko, M.; Govsieiev, D.; Gromova, O.; Martinova, I.; Tyan, O. (Journal of Education, Health and Sport, 2016)
Makarenko M., Govsieiev D., Gromova O., Martinova L., Tyan O. Хірургічна корекція істміко-цервікальної недостатності при невиношуванні вагітності = Surgical correction of isthmic-cervical insuffiency at miscarriage of pregnancy. Journal of Education, Health and Sport. 2016;6(7):164-172. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57302 http://ojs.ukw.edu.pl/index.php/johs/article/view/3675 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.06.2016. Revised 09.07.2016. Accepted: 09.07.2016. УДК: 618.3:618.146-008.64-089.84 ХІРУРГІЧНА КОРЕКЦІЯ ІСТМІКО-ЦЕРВІКАЛЬНОЇ НЕДОСТАТНОСТІ ПРИ НЕВИНОШУВАННІ ВАГІТНОСТІ М. В. Макаренко, Д. О. Говсєєв, О. Л. Громова, Л. І. Мартинова, О. В. Тян Національний медичний університет імені О.О.Богомольця, Київ, Україна SURGICAL CORRECTION OF ISTHMIC-CERVICAL INSUFFIENCY AT MISCARRIAGE OF PREGNANCY M. Makarenko, D. Govsieiev, O. Gromova, L. Martinova, O. Tyan National Medical University named O.O. Bohomolets Article This article is dedicated to the surgical methods of treatment of isthmic-cervical insufficiency. Basic risk of the origin of this pathology factors are presented; the analysis of existent methodologies of treatment is conducted. The following conditions are presented : the terms of realization of operations of cervical cerclage, contra-indications that are specified to surgical treatment, and possible complications. Methodology of cervical cerclage is described by application of mersilen ligature, and its advantages before the emergence of the traditional methodologies. The use of surgical suture in the cervix is discussed after 24 weeks of pregnancy. Local protocol that is used in the maternity hospital №of 5 ofKievis described, in obedience to that, the stitching on the cervix of the uterus conducted also in a term after 26 weeks of pregnancy. Statistical data is also presented, it confirms the expediency of the use of cervical cerclage with a mersilen ligature and its realization in terms after 26 weeks of pregnancy. Keywords: cervical cerclage, mersilenovaya thread, ultrasound, obstetric pessary. ХИРУРГИЧЕСКАЯ КОРРЕКЦІИЯ ИСТМИКО-ЦЕРВИКАЛЬНОЙ НЕДОСТАТОЧНОСТИ ПРИ НЕВЫНАШИВАНИИ БЕРЕМЕННОСТИ М. В. Макаренко, Д. А. Говсеев, А. Л. Громова, Л. И. Мартынова, О. В. Тян Национальный медицинский университет имени А.А.Богомольца, Киев, Украина Данная статья посвящена хирургическим методам лечения истмико-цервикальной недостаточности. Приводятся основные факторы риска возникновения данной патологии, проводится анализ существующих методик лечения. Указываются условия проведения операций серкляж, противопоказания к хирургическому лечению, возможные осложнения. Описывается методика серкляжа с применением мерселеновой нити, и ее преимущества перед существующими традиционными методиками. Дискутируется по поводу применения хирургического шва на шейку матки в сроки после двадцати четырех недель беременности. Описывается локальный протокол, который применяется в роддоме №5 г. Киева, согласно которому наложения шва на шейку матки проводится и в сроке после двадцати шести недель беременности. Приводятся статистические данные, подтверждающие целесообразность использования серкляжа с мерселеновую нитью и его проведения в сроки после двадцати шести недель беременности. Ключевые слова: цервикальный серкляж, мерселеновая нить, ультразвуковое исследование, акушерський пессарий.